Keracunan Pestisida pada Petani Penyemprot Cabe di Desa Candi Kecamatan Bandungan Kabupaten Semarang - Afriyanto, Afriyanto; Nurjazuli, Nurjazuli; Budiyono, Budiyono (Jurnal Kesehatan Lingkungan Indonesia, 2009)
ABSTRACT Background: The farmer of chilli often used pesticide in combination and using no  exact dose with reasoing n to increase the potentiality to plant diseases. This condition was harmful for human health, especially the sprayer of chili farmer that can  cause acute poisoning. One of the method to detect of pesticide poisoning was by checking the choliesterase activity in blood. The effect of the exixtance of pesticide in human body was obstructed enzym cholinesterase. This research aimed to analyze risk factors related to pesticide poisoning on the sprayer of chilli farmer in Bandungan Semarang. Method: It was an observational research  using cross-sectional design. The population of study were 110 sparyer of chilli farmers. Using proportional simple random sampling, It was taken 50 farmers.The variable studied in this research were knowledge, attitude, BMI, kind of pesticides, pesticide dose, duration of spray, frequency of spraying, spraying related to wind direction, personal hygiene and personal protective equipment use, and blood examnation to detect cholinestarase using Spectrophotometer. The data would be analyzed using Chi-square test and logistic regression method. Result: The research showed that there were 13  farmers (26%) who suffered severepoisoning and 37  farmers (74%) were suffered light poisoning. The risk  factors related to pesticide poisoning were knowledge, attitude, number of  pesticides used, pesticide dose, frequency of spraying, wind direction, personal hygiene and personal protective equipment use. Conclusion: Most of the chill farmer had suffered poisoning, although It was light. It was needed to improve the behaviour of chilli farmer in handling and spraying activity.   Key words: Chilli farmer, cholinesterase activity, organophosphate poisoning, Bandungan.